Dynamic bandwidth allocation EPON survey - Radzi N.A.M.; Din N.M.; Sadon S.K.; Al-Mansoori M.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
One of the best options to support fiber to the home is Ethernet passive optical network (EPON) as it provides high bandwidth as well as it is cost effective. However, the issues arise in the EPON system nowadays is the bandwidth allocation. There are numerous research works that are able to allocate the upstream bandwidth dynamically to the optical network units (ONUs). In this paper, we compile and classify these research works in order to provide the state-of-art of the dynamic bandwidth allocation algorithm (DBA). The classifications provide perceptive presentations of the previous research works on EPONs. The survey allows the researchers to better understand the DBA research quickly. 2013 IEEE.